BIOCHEMICAL ANALYSIS OF CULTURAL SPECIES OF TRITICUM L. AND SECALE L. (Experimental biology, 2022)
In the article Triticum L. and Secale L. to clarify the bioecological features of the species, the chemical composition of a number of varieties containing macronutrients, proteins, fats, carbohydrates, fiber and vitamins was determined.The study included varieties of winter soft wheat "Mereke 70" and " Dimash "and winter durum wheat" Kazakhstansky yantar ", winter rye Tretikale" Taza", cultivated in the regions of Almaty and Zhambyl regions.